A Study on the Relationship Between Eggshell Color and Eggshell Quality in Commercial Broiler Breeders - Ingram, D.R.; Hatten, L.F.; Homan, K.D. (International Journal of Poultry Science, 2008)
In this experiment, two trials were conducted to determine whether broiler breeder eggshell color could be used as an easy means of predicted eggshell quality. In Trial 1, 4320 commercial broiler breeder eggs were obtained. Specific gravity (SG) was measured and color determined on the eggs on the day of lay. The results showed that eggshell color was significantly affected by age and strain. L was found to be the most closely related to total color, E. Eggshell color was highly significantly but lowly correlated to SG. In Trial 2, 360 commercial broiler breeder eggs were acquired. SG and color were determined on the day of lay. Shell thickness without the membranes was then measured. In this trial, eggshell color was found to also be highly significantly but lowly correlated to shell thickness. It was determined that, while eggshell color is significantly correlated to shell quality, it is not as accurate a measure of eggshell quality as is SG or shell thickness.